2019
DOI: 10.1021/acsomega.8b03204
|View full text |Cite
|
Sign up to set email alerts
|

Surface Coupling of Octaethylporphyrin with Silicon Tetrachloride

Abstract: The surface assembly of 2,3,7,8,12,13,17,18-octaethylporphyrin (OEP) using silicon tetrachloride as a coupling agent was investigated using atomic force microscopy (AFM). Nanopatterned films of Si-OEP were prepared by protocols of colloidal lithography to evaluate the morphology, thickness, and molecular orientation for samples prepared on Si(111). The natural self-stacking of porphyrins can pose a challenge for molecular patterning. When making films on surfaces, porphyrins will self-associate to form co-plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 97 publications
0
1
0
Order By: Relevance
“…Previous studies have reported that the planar macrocycles are oriented in a cofacial arrangement to form multilayer films on flat substrates [70,75]. The assembly process to generate porphyrin multilayers was monitored with UV/Vis spectroscopy and the bond length between the stacked aromatic ring was investigated with X-ray diffraction studies, as reported by Lee et al [75].…”
Section: Encapsulation Of Metal Nanoparticles With Siloxane-linked Po...mentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have reported that the planar macrocycles are oriented in a cofacial arrangement to form multilayer films on flat substrates [70,75]. The assembly process to generate porphyrin multilayers was monitored with UV/Vis spectroscopy and the bond length between the stacked aromatic ring was investigated with X-ray diffraction studies, as reported by Lee et al [75].…”
Section: Encapsulation Of Metal Nanoparticles With Siloxane-linked Po...mentioning
confidence: 97%
“…The orientation of porphyrins on surfaces is determined by factors such as the nature of the peripheral substituents and their position on the macrocycle. The strategy of preparing a coplanar, skewered arrangement of OEP multilayers that are mediated by covalent Si-O bonds has been previously described [70]. Herein, we present results for linking porphyrins with Si-O-Si bridges to metal nanoparticles.…”
Section: Introductionmentioning
confidence: 98%
“…In recent years, with the wide application of high-power lasers, nonlinear optical (NLO) materials have received significant attention as they can protect the human eyes and sensors from high-power lasers. Among numerous NLO materials, porphyrin (Por) has been widely investigated due to its unique 18 π electron conjugated structure [1], good thermal stability and narrow bandgap [2]. It is reported that modifying porphyrins with carbon nanomaterials could form nanohybrids and enhance NLO properties by synergic effect [3,4].…”
Section: Introductionmentioning
confidence: 99%